Superheroes and the mythic imagination: order, agency and politics. Issue 5 (3rd September 2021) - Curtis, Neal
ABSTRACT: This article explores the relationship between superhero comics and myth. It argues that traditional approaches to myth see it as a deeply conservative form, and applying it to the superhero genre makes the comics seem more conservative than they are. This also is inadequate if we are to understand the politics of superhero comics, which is currently focussed on issues of representation and diversity, something that is in turn being contested by reactionary forces collected under the name 'Comicsgate'. To understand what is happening we need to challenge the conservative view of myth seen in the writing of Eco and Reynolds, and supplement this with a generative view of myth found in the work of Cassirer, Castoriardis, and Bloch. Here, myth is actually integral to the creation of a world. It is what enables us to make sense of the things around us and find our place. If these myths are no longer circulated or our challenged our place in the world is also threatened. To understand how this is worked out today I finally apply Barthes work on myth to Chelsea Cain's run on Mockingbird to show how the comic challenged the myth and the ideology of patriarchy.